The Influence of Information Security Management on Operational Performance of Humanitarian Value Chains in Arid and Semi-Arid Lands of Kenya - Wachieni, Lindsay Nyawira; Muthini, Jackson Ndolo; Ndungu , Charles K; Mwangi , Moses (International Journal of Supply Chain and Logistics, 2023)
Purpose: Managements of humanitarian organizations in arid and semi-arid lands have recently become sensitized to the vulnerability of their supply chains. This is due to an ever-increasing range of security breaches and disruptions that affect global value chains especially in information security management. The current study sought to determine the influence of information security management on the operational performance of humanitarian value chains in arid and semi-arid lands of Kenya. Methodology: The study adopted a cross-sectional design. A target population of 100 respondents was studied through census method from humanitarian organizations operating in arid and semi-arid lands of Kenya. A semi-structured questionnaire was used to collect information whereas descriptive and inferential statistics were used to analyze the data. The results were presented by use of tables. Findings: Scrutiny of the results of linear regression analysis indicated that information security management significantly predicted the operational performance of the organizations (r=.659, p=0.000). Unique contribution to theory, practice and policy: The study recommends that humanitarian organizations should put measures into place to ensure access control and safe storage of information. Employees should also be trained in information security management to understand their role on overall organizational performance.